Family in person formation: or the importance of early attachment in human development - Berástegui Pedro-Viejo, Ana (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The aim of this paper is to present the importance of family in the formation of the person. First, we develop a brief history of the discovery of attachment as a primary need, second, we describe the attachment system as a humanizing factor for the baby and third, we develop the idea that family is the group who can better offer that kind of bonding throughout the development. Finally, we state the grounds of Primera Alianza, a program designed to strengthen attachment relationships in at risk families.